Do predator attacks on productive species and the respective economic losses influence the psychological distress of farmers in Uruguay? A cross-sectional study - Paul Ruiz; Gustavo Benítez; Pablo Ernesto Bobadilla; Maximiliano Piedracueva; Juan Pablo Damián (Rural and Remote Health, 2024)
Introduction: In Uruguay, productive animals are attacked by various predators, causing injuries and financial losses, leading to great concern for farmers. The objective of this study was to determine, using a cross-sectional study, if predator attacks on productive animals during the year 2021 influenced the psychological distress of farmers. Methods: Four hundred and forty-two farmers from around the country were surveyed with questions according to the Kessler Psychological Distress Scale (dependent variable), and predator attacks received in 2021 (independent variable). Results: Of the total number of farmers surveyed, approximately 49% (216/442) had animals that had been attacked by predators. Farmers whose productive species were attacked in 2021 had higher levels of psychological distress than those whose animals were not attacked (p<0.01). Additionally, farmers who reported the highest levels of psychological distress had more deaths of productive species (and more financial losses) from predator attacks in 2021 than those who did not. Conclusion: The losses of productive species and the financial costs negatively influenced the psychological distress of farmers. This information highlights the need to generate public policies about farmers wellbeing that help them in these situations.